AN OPTIMAL CONTROL FORMULATION OF PORTFOLIO SELECTION PROBLEM WITH BULLET TRANSACTION COST - SYAHRIL, E. (MILANG Journal of Mathematics and Its Applications, 2003)
This paper formulates a consumption and investment decision problem for an individual who has available a riskless asset paying ﬁxed interest rate and a risky asset driven by Brownian mo- tion price ﬂuctuations. The individual is supposed to observe his or her current wealth only, when making transactions, that trans- actions incur costs, and that decisions to transact can be made at any time based on all current information. The transactions costs is ﬁxed for every transaction, regardless of amount trans- acted. In addition, the investor is charged a ﬁxed fraction of total wealth as management fee. The investor’s objective is to max- imize the expected utility of consumption over a given horizon. The problem faced by the investor is formulated into a stochastic discrete-continuous-time control problem.